2017
DOI: 10.1080/14767058.2017.1311314
|View full text |Cite
|
Sign up to set email alerts
|

Safety of peripherally inserted central catheters during pregnancy: a retrospective study

Abstract: In contrast with previous studies, we report a complication rate associated with peripheral line use in pregnant and postpartum women that appears similar to that in non-pregnant populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
10
1
1
Order By: Relevance
“…The incidence of PICC‐RT varies by patient population (Fallouh et al., 2015). Studies conducted in cancer patients reported a rate of 4% to 51% (Aw et al., 2012; Bertoglio et al., 2016; Kang, Chen, et al., 2017; Liu et al., 2015), higher than the non‐cancer populations (2%–5%) (Chopra et al., 2013, 2018; Jacques et al., 2018). The incidence of PICC‐RT in patients with lung cancer remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of PICC‐RT varies by patient population (Fallouh et al., 2015). Studies conducted in cancer patients reported a rate of 4% to 51% (Aw et al., 2012; Bertoglio et al., 2016; Kang, Chen, et al., 2017; Liu et al., 2015), higher than the non‐cancer populations (2%–5%) (Chopra et al., 2013, 2018; Jacques et al., 2018). The incidence of PICC‐RT in patients with lung cancer remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Totally 112 patients were enrolled in the study and infection rate was 3.6%. In total, the complication rates in this population were similar to that in non-pregnant population [12].…”
Section: Literature Retrievedmentioning
confidence: 64%
“…A similar conclusion was recently reached with regard to peripherally inserted catheters in pregnancy and puerperium. 8 Regarding patients with an AV access, an interesting case report 9 warns against the risk of development of fistula aneurysms in pregnancy, but the frequency of this complication is still unknown, and we suggest that patients already treated with an AV access should continue to do so, with careful observation of the access.…”
mentioning
confidence: 91%
“…A similar conclusion was recently reached with regard to peripherally inserted catheters in pregnancy and puerperium. 8…”
mentioning
confidence: 99%